Ontogenic, Phenotypic, and Functional Characterization of XCR1+ Dendritic Cells Leads to a Consistent Classification of Intestinal Dendritic Cells Based on the Expression of XCR1 and SIRPα - Becker, Martina; Güttler, Steffen; Bachem, Annabell; Hartung, Evelyn; Mora, Ahmed; Jäkel, Anika; Hutloff, Andreas; Henn, Volker; Mages, Hans Werner; Gurka, Stephanie; Kroczek, Richard A. (Frontiers in Immunology, 2014)
In the past, lack of lineage markers confounded the classification of dendritic cells (DC) in the intestine and impeded a full understanding of their location and function. We have recently shown that the chemokine receptor XCR1 is a lineage marker for cross-presenting DC in the spleen. Now we provide evidence that intestinal XCR1+ DC largely, but not fully, overlap with CD103+ CD11b- DC, the hypothesized correlate of “cross-presenting DC” in the intestine, and are selectively dependent in their development on the transcription factor Batf3. XCR1+ DC are located in the villi and epithelial crypts of the lamina propria of the small intestine, the T cell zones of Peyer’s Patches, and in the T cell zones and sinuses of the draining mesenteric lymph node. Functionally, we could demonstrate for the first time that XCR1+ / CD103+ CD11b- DC excel in the cross-presentation of orally applied antigen. Together, our data show that XCR1 is a lineage marker for cross-presenting DC also in the intestinal immune system. Further, extensive phenotypic analyses reveal that expression of the integrin SIRPα consistently demarcates the XCR1- DC population. We propose a simplified and consistent classification system for intestinal DC based on the expression of XCR1 and SIRPα.